Games For Education: Peningkatan Kemampuan Digital Guru di SMK Amal Bakti, Jatimulyo - Afrianto; Rahmanto, Yuri; Wahyudin, Achmad Yudi; Fatriana, Nina; Damayanti, Silvia; Kinanti, Anggun Putri (FKIP Universitas Majalengka, 2023)
Innovative and interesting learning is an important requirement in the current educational context. One alternative way is to apply games by means of the Wordwall application as a learning digital tool. This article focuses on community service in implementing Wordwall in learning and explores its benefits in an educational context. The methods used include counseling, training, and assisting in using Wordwall in the classroom. The results of community service show that the use of Wordwall in learning can increase student participation, learning motivation, and understanding of concepts. In addition, the use of Wordwall also provides an opportunity for teachers to integrate technology into learning, increases creativity in compiling learning content, and provides an interesting learning experience for students. However, there are also some challenges encountered in using Wordwall, such as limited access to technology and teacher expertise in using the application. Therefore, suggestions for teachers in using games for education, such as Wordwall, include increasing teachers' digital competence, selecting and developing learning content according to student needs, and monitoring the impact of using games for education. This article is expected to provide insights and recommendations for teachers in utilizing Wordwall as an innovative and effective learning support tool.